2015
DOI: 10.5194/bg-12-1271-2015
|View full text |Cite
|
Sign up to set email alerts
|

Size-fractionated dissolved primary production and carbohydrate composition of the coccolithophore <i>Emiliania huxleyi</i>

Abstract: Abstract. Extracellular release (ER) by phytoplankton is the major source of fresh dissolved organic carbon (DOC) in marine ecosystems and accompanies primary production during all growth phases. Little is known, so far, on size and composition of released molecules, and to which extent ER occurs passively, by leakage, or actively, by exudation. Here, we report on ER by the widespread and bloomforming coccolithophore Emiliania huxleyi grown under steady-state conditions in phosphorus-controlled chemostats (N :… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 91 publications
0
42
0
Order By: Relevance
“…These groups are known to be strong TEP producers (Engel, 1998; (b) α = 2.25 and β = 0.65, (Hong et al, 1997); (c) α = 2.27 and β = 0.24, (Yamada et al, 2015); (d) α = 2.06 and β = 0.50, (Ramaiah and Furuya, 2002); (e) α = 1.63 and β = 0.39, (Passow and ; (f) α = 1.63 and β = 0.32, (Corzo et al, 2005); (g) α = 1.08 and β = 0.38, (Ortega-Retuerta et al, 2009b). (Passow and Alldredge, 1994), and besides, previous studies have shown that TEP production rates reach maxima at late stages of the growth cycle, once nutrients have been exhausted (Corzo et al, 2000;Pedrotti et al, 2010;Borchard and Engel, 2015). In the CU, the relatively low Chl a level along with low silicate concentrations suggests that the upwelling-triggered bloom maximum had already passed, which resulted in a high TEP : Chl a ratio.…”
Section: Main Drivers Of Tep Distribution In the Surface Oceanmentioning
confidence: 92%
“…These groups are known to be strong TEP producers (Engel, 1998; (b) α = 2.25 and β = 0.65, (Hong et al, 1997); (c) α = 2.27 and β = 0.24, (Yamada et al, 2015); (d) α = 2.06 and β = 0.50, (Ramaiah and Furuya, 2002); (e) α = 1.63 and β = 0.39, (Passow and ; (f) α = 1.63 and β = 0.32, (Corzo et al, 2005); (g) α = 1.08 and β = 0.38, (Ortega-Retuerta et al, 2009b). (Passow and Alldredge, 1994), and besides, previous studies have shown that TEP production rates reach maxima at late stages of the growth cycle, once nutrients have been exhausted (Corzo et al, 2000;Pedrotti et al, 2010;Borchard and Engel, 2015). In the CU, the relatively low Chl a level along with low silicate concentrations suggests that the upwelling-triggered bloom maximum had already passed, which resulted in a high TEP : Chl a ratio.…”
Section: Main Drivers Of Tep Distribution In the Surface Oceanmentioning
confidence: 92%
“…6, dashed line) and death (j DOC,D , Fig. 6, dash-dot line), which reflect the passive diffusion of small (<10 kDa) mono and polysacharides, rich in glucose and/or the DOC fraction of the 5 dissolved aminoacids or other phosphorus-containing organic molecules, (Bjørnsen, 1988;Urbani et al, 2005;Flynn et al, 2008;Borchard and Engel, 2015). Moreover, DOC H , is associated with j DOC,R flux (Fig.…”
Section: Molecular Composition and Size Of Dom Releasedmentioning
confidence: 95%
“…Moreover, DOC H , is associated with j DOC,R flux (Fig. 6, solid line) and reflects the active exudation of DOC due to nutrient limitation, mainly composed of high molecular weight carbohydrates (>10kDa) such as heteropolysacharides or organic carbon associated with the organic forms of nitrogen and phosphate exuded by the cell due to unbalanced growth (Fogg, 1983;Urbani et al, 2005;Flynn et al, 2008;Borchard and Engel, 2015). According to model results, 10 during the nutrient-replete phase, in both scenarios, the main fraction of total DOC (TDOC) is almost entirely comprised by low molecular weight DOC L (mean throughout the nutrient-replete phase: 95 %, Fig.…”
Section: Molecular Composition and Size Of Dom Releasedmentioning
confidence: 99%
“…In order to explain what ligands condition the oxidation process, it is advised to perform detailed studies of Fe(II) oxidation with individual model ligands. DUA E account for an important fraction of the DOC E , ranging between 1 and 5% of the DOC released by E. huxleyi under different simulated pH conditions (Borchard and Engel, 2015;Samperio-Ramos et al, 2017). Thus, to elucidate the role played by DUA E in the SWEX, the next series of experiments were carried out using a simplified ligand model (i.e., glucuronic acid as DUA) in artificial seawater (ASW).…”
Section: Doc Dependencementioning
confidence: 99%
“…In order to explain the key role played by the FeCHO + complex on speciation and overall oxidation rate of Fe(II) in SWEX, we assumed the equilibrium constants and the individual oxidation rate estimated with the DUA model ligand in section Oxidation rate in presence of uronic acids. Uronic acids derived from hexoses (i.e., glucuronic and galacturonic acids) are the main class of sugar acids present in the E. huxleyi exudates (Borchard and Engel, 2015) and, therefore the DUA E , measured in the SWEX ( Figure S2) were considered as hexuronic acids in the model (Table 1). Additionally, to describe the role played by the organic pool ligands in the Fe(II) redox behavior, a non-specific type ligand (denoted as L) was also included in the modeling approach.…”
Section: Kinetic Model Considering Exudates Of E Huxleyi Produced Unmentioning
confidence: 99%